Ecological studies in coastal sand dune rangelandsin the north-west of Egypt - Abbas M.S.; El Morsy M.H.; Shahba M.A.; Moursy F.I. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
The present work was carried out in coastal sand dunes along the north-west coast of Egypt during the springs of 2005 and 2006 in order to study the relationships between some common range plants and environmental factors, in terms of botanical structure, productivity, nutritive value and their ability to sustain and renew themselves in coastal sand dune habitats. Twenty-four plant species were identified belonging to sixteen families. According to palatability, fifteen species (about 62.5%) were palatable and nine species (about 37.5%) were unpalatable. In terms of life duration, twenty plant species were perennials (about 83%) and only four species (about 17%) were annuals. The studied characteristics of range plants were frequency, abundance, plant density, cover percentage, importance value and productivity. All characteristics showed differences between plants in coastal sand dune habitats.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)